Caspase-2 mediated apoptotic and necrotic murine macrophage cell death induced by rough Brucella abortus. - Fang Chen; Yongqun He (PLoS ONE)
Brucella species are Gram-negative, facultative intracellular bacteria that cause zoonotic brucellosis. Survival and replication inside macrophages is critical for establishment of chronic Brucella infection. Virulent smooth B. abortus strain 2308 inhibits programmed macrophage cell death and replicates inside macrophages. Cattle B. abortus vaccine strain RB51 is an attenuated rough, lipopolysaccharide O antigen-deficient mutant derived from smooth strain 2308. B. abortus rough mutant RA1 contains a single wboA gene mutation in strain 2308. Our studies demonstrated that live RB51 and RA1, but not strain 2308 or heat-killed Brucella, induced both apoptotic and necrotic cell death in murine RAW264.7 macrophages and bone marrow derived macrophages. The same phenomenon was also observed in primary mouse peritoneal macrophages from mice immunized intraperitoneally with vaccine strain RB51 using the same dose as regularly performed in protection studies. Programmed macrophage cell death induced by RB51 and RA1 was inhibited by a caspase-2 inhibitor (Z-VDVAD-FMK). Caspase-2 enzyme activation and cleavage were observed at the early infection stage in macrophages infected with RB51 and RA1 but not strain 2308. The inhibition of macrophage cell death promoted the survival of rough Brucella cells inside macrophages. The critical role of caspase-2 in mediating rough B. abortus induced macrophage cell death was confirmed using caspase-2 specific shRNA. The mitochondrial apoptosis pathway was activated in macrophages infected with rough B. abortus as demonstrated by increase in mitochondrial membrane permeability and the release of cytochrome c to cytoplasm in macrophages infected with rough Brucella. These results demonstrate that rough B. abortus strains RB51 and RA1 induce apoptotic and necrotic murine macrophage cell death that is mediated by caspase-2. The biological relevance of Brucella O antigen and caspase-2-mediated macrophage cell death in Brucella pathogenesis and protective Brucella immunity is discussed.